Construct Validity and Test–Retest Reliability of Questionnaires to Assess Workplace Violence Risk Factors (QAWRF): A Tripartite Perspective of Worksite-Specific Determinants in Healthcare Settings - Mohd Hatta FH; Samsudin EZ; Aimran N; Ismail Z; Mohd Sapian NA (Risk Management and Healthcare Policy, 2024)
Faizul Haris Mohd Hatta,1 Ely Zarina Samsudin,1 Nazim Aimran,2 Zaliha Ismail,1 Nor Akmar Mohd Sapian3 1Department of Public Health Medicine, Universiti Teknologi MARA, Sungai Buloh, Selangor, Malaysia; 2College of Computing, Informatics, and Mathematics, Universiti Teknologi MARA, Shah Alam, Selangor, Malaysia; 3Quality Unit, Kemaman Hospital, Terengganu State Health Department, Chukai, Terengganu, MalaysiaCorrespondence: Ely Zarina Samsudin, Email elyzarina07@yahoo.comIntroduction: Among available workplace violence (WPV) interventions, only data-driven, worksite-based, and risk-based approach WPV interventions had moderate evidence for effectiveness in decreasing the risk of WPV. The Questionnaires to Assess Workplace Violence Risk Factors (QAWRF) had been previously developed to determine the level of WPV risk factors in each healthcare setting based on the tripartite perspective of key stakeholders to enable effective WPV interventions. This study aimed to determine the construct validity and test–retest validity of QAWRF.Methods: QAWRF, a three-component instrument consisting of QAWRF-Administrators, QAWRF-Workers, and QAWRF-Clients, had previously undergone content validation, face validation, and internal consistency reliability testing. 965 respondents were recruited to examine the construct validity of QAWRF, and a subset of these (n = 90) were retested again at an interval of three weeks to assess its test–retest reliability. Confirmatory factor analysis (CFA) was performed, and fitness indices, average variance extracted, correlation coefficient, composite reliability, and intraclass correlation coefficient were determined.Results: QAWRF-Administrator, QAWRF-Worker, and QAWRF-Client had acceptable factor loadings (≥ 0.6), absolute fit (Root Mean Square Error of Approximation > 0.1), incremental fit (Confirmatory Fit Index and Tucker Lewis Index > 0.9), parsimonious fit (Chi-square/degree of freedom < 5), correlation coefficient between construct (≤ 0.85), discriminant validity index, and construct reliability (≥ 0.6). CFA supported a four-factor model for QAWRF-Administrator and QAWRF-Worker, and a two-factor model for QAWRF-Client.Conclusion: QAWRF holds good construct validity and test–retest reliability. By using QAWRF, healthcare managers can identify specific WPV risk factors that are perceived by stakeholders as prevalent at a particular workplace, and these findings can contribute towards data-driven, worksite-specific, and targeted WPV interventions in healthcare settings that are expected to be resource-efficient and more effective than general WPV interventions.Keywords: workplace violence, risk factors, risk assessment, questionnaire, instrument, tool, validation, healthcare workers